STEAM-BASED ISLAMIC EDUCATION LEARNING DESIGN TO IMPROVE THE 21ST CENTURY COMPETENCIES OF ELEMENTARY SCHOOL STUDENTS - Fuad Ahmad Riva'i; Ade Falah; Afaf Saifullah Kamalie; Fatimah Habibatulhaq; Nadia Oktaviani (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to develop and examine the effectiveness of a STEAM-based (Science, Technology, Engineering, Arts, Mathematics) instructional design in Islamic Religious Education (PAI) to enhance 21st-century competencies among elementary school students. The research employed a Design-Based Research (DBR) approach involving 37 fifth-grade students. Data were collected through pretest–posttest assessments, observations, interviews, and questionnaires, and analyzed using mixed methods. Quantitative findings revealed a significant increase in mean scores from 98.38 (moderate category) to 155.89 (high category), with an N-Gain score of 0.62 (moderate to high) and a large effect size (Cohen’s d = 3.402). A paired-sample t-test indicated a statistically significant difference (p < 0.05) between pretest and posttest results. Qualitative findings demonstrated improvements in students’ active participation, creativity, collaboration, communication, and digital literacy, alongside a shift in teachers’ roles toward facilitators of learning. The integration of quantitative and qualitative results confirms that STEAM-based PAI learning is effective, contextual, and relevant in fostering 4C skills and digital literacy. This model is recommended as an innovative approach for developing Islamic education curricula at the elementary level